Solvent detergent vs. fresh frozen plasma in cirrhotic patients undergoing liver transplant surgery: a prospective randomized control study. Issue 2 (28th February 2013) - Bindi, M. L.; Miccoli, M.; Marietta, M.; Meacci, L.; Esposito, M.; Bisà, M.; Mozzo, R.; Mazzoni, A.; Baggiani, A.; Scatena, F.; Filipponi, F.; Biancofiore, G.
<x xml:space="preserve">Abstract</x> Background Although orthotopic liver transplantation (OLT) is nowadays considered standard practice at experienced centres, it can still be affected by a significant risk of massive bleeding and its related complications. Solvent/detergent plasma (S/D Plasma) has been proposed as an alternative to fresh frozen plasma (FFP) to curtail such complications. This study aimed at evaluating the efficacy of S/D Plasma in OLT patients by comparing it to FFP. Materials and Methods Sixty‐three OLT patients were randomized into two groups depending on whether they were transfused with FFP or S/D plasma. A thromboelastography‐based protocol aimed at achieving and maintaining predetermined coagulation goals was used to guide plasma transfusions. At the beginning and the end of surgery, standard laboratory coagulation tests were performed together with the assessment of the VII, VIII, V, XII factors and S protein blood levels. Results The two study groups equally achieved the thromboelastography goals but with a reduced amount of transfusions in the S/D plasma group (P < 0·0001). At the end of surgery, factors V and XII and S protein blood levels were lower in the S/D plasma patients who also showed lower INR, aPTT and antithrombin III levels. Conclusion In cirrhotic patients undergoing OLT, the use of S\D plasma associated with thromboelastography allows the same clinical results but with a significant reduction in the amount of plasma transfusions.